Fiqh Aqalliyat: the Endeavor for the Well-Being of Muslims as a Minority - Muazzam Khairi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Fiqh Aqalliyat: The Endeavor for the Well-Being of Muslims as a Minority. Fiqh Aqalliyat (Minority Jurisprudence) is a contemporary branch of Islamic legal studies that has emerged in response to the reality of Muslims living as minorities in non-Muslim countries. This situation gives rise to various social, political, and religious challenges that are not fully accommodated by classical fiqh, which was developed within the context of majority Muslim societies. Fiqh Aqalliyat therefore presents itself as a form of modern ijtihad (independent legal reasoning) that seeks to prioritize the welfare of the community through a contextual and flexible approach while remaining grounded in the foundational principles of Islam. This study employs a qualitative method with a literature review approach to explore the concept, its shar'i foundations, and its application in the lives of Muslim minorities. The findings indicate that Fiqh Aqalliyat is not intended to replace established Islamic law, but rather serves as an adaptation to the challenges posed by different times and places. Principles such as maslahah mursalah (unrestricted public interest), rukhsah (legal dispensation), and taghayyur al-fatwa (change of legal opinion) constitute the primary foundations in formulating rulings relevant to minority contexts. Accordingly, Fiqh Aqalliyat serves as a vital instrument in maintaining the balance between Islamic integrity and social engagement within pluralistic societies. This study recommends further academic and practical development of Fiqh Aqalliyat so that it may become an applicable and effective solution for Muslim communities across the globe.